The Psychodynamics of Enlightened Leadership Coping with Chaos - Mitroff, Ian I.; Kilmann, Ralph H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access book provides a comprehensive look at the pluses and minuses of leadership in times of an unparalleled crisis, such as the COVID-19 global pandemic. It examines the COVID-19 crisis in terms of psychodynamics, crisis management, and especially from the standpoint of complex, messy systems. It analyses how leaders need to think and act differently to cope better with$1 (Bunfortunately not prevent$1 (Bfuture crises.s
Chapter 1. Wrestling with The Inner Demons of Contemporary Life: A Brief Overview of Psychoanalytic Thought -- Chapter 2. Crises: A Major Systems Problem -- Chapter 3. Wicked Messes: The Ultimate Challenge to Reality. Chapter 4. Inquiry Systems: How Do We Know What We Need to Know?- Chapter 5. Inquiry Systems as Coping Mechanisms -- Chapter 6. The Coronavirus, A Jungian Analysis -- Chapter 7. Assumptional Analysis -- Chapter 8. Heuristics and Meta-Heuristics for Coping with Messes -- Chapter 9. Changing the Culture of Policing: A Moral Imperative! -- Chapter 10. The Choice Is Between Mental Health and Mental Illness -- Chapter 11. Enlightened Leadership for Coping with Chaos.
Keywords: Strategic planning; Leadership; Psychology, Industrial; Industries; Business Strategy and Leadership; Organizational Psychology; Industries